The Influence Of Academic Supervision And Organizational Culture On The Work Motivation Of Educators - Chelsi Hestivik; Syafaruddin Syafaruddin; Muhammad Fitriyadi (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
Teacher work motivation plays a fundamental role in improving instructional quality and achieving educational objectives. Nevertheless, low teacher motivation remains evident despite the implementation of academic supervision and the establishment of supportive organizational cultures in schools. This study aimed to examine the effects of academic supervision and organizational culture on teachers' work motivation at public junior high schools in Siak Hulu District, Kampar Regency. A quantitative correlational research design was employed. The sample consisted of 88 teachers selected through probability sampling using the Slovin formula from a population of 113 teachers. Data were collected using validated and reliable five-point Likert-scale questionnaires and analyzed through multiple linear regression using IBM SPSS version 26. The findings revealed that academic supervision had a positive and significant effect on teachers' work motivation (β = 0.412; t = 4.872; p < 0.001). Organizational culture also demonstrated a positive and significant influence on work motivation (β = 0.365; t = 3.965; p < 0.001). Simultaneously, both variables significantly affected teacher motivation (F = 38.721; p < 0.001) and explained 46.8% of the variance in work motivation (R² = 0.468). These findings indicate that collaborative academic supervision combined with a supportive organizational culture constitutes an effective managerial strategy for strengthening teachers' work motivation and enhancing the overall quality of educational services